The Effect of Mycorrhiza Application and Phosphorus Addition on AMF Spores Density and Pueraria javanica Growth - Rosita, Risa; Suryadi, Jennifer Claudia; Eris, Deden Dewantara (SEAMEO BIOTROP, 2025)
One of the suitable host plants for AMF (Arbuscular Mycorrhizal Fungi) is Pueraria javanica. Several factors that can affect the growth of P. javanica are the availability of nutrients and the activity of potential soil microbes, such as AMF. Applying potential soil microbes (AMF) to plants can increase plant growth, chlorophyll levels, and enzyme activity, and even improve soil quality. The ability of AMF to increase plant nutrient absorption causes plants with AMF tend to have optimum growth. The study aimed to understand the effect of AMF application and phosphorus (P) nutrients addition on AMF spore density and P. javanica growth. The experiment used a completely randomized design with one factor (formulation). Results of the study proved that phosphorus (P) addition was able to reduce AMF spore densities (Glomus etunicatum and Glomus mosseae) 3 weeks after application (WAA). The availability of P in a fairly high amount around the root area caused plants to reduce their dependence on AMF, which resulted in a decrease in AMF colonization and AMF spore densities. On the other hand, adding P nutrients proved to increase growth parameters (plant height and number of leaves) of P. javanica because AMF helped the absorption of P and received carbon from plants in return. Treatment P6 (G. etunicatum 10 g + without phosphorus) had the highest spore density value (400.33/10 g planting media), and treatment P9 (G. mosseae 10 g + phosphorus 10 ppm) showed the highest increase in plant height of 13.333 (P < 0.05) 3 weeks after application. Meanwhile, the maximum increase in the number of leaves occurred in plants that received 10 g of G. mosseae and 10 ppm of P every two days for three weeks. Studying AMF spore density can significantly improve plant growth, agronomic efficiency, and agricultural sustainability.